De onthulling kennismaking met een collectie = Die Enthüllung : die Entdeckung einer Sammlung = The unveiling : discovering a collection - Vloten, Francisca van 1950- (De Factory, 2022)
The Exhibition 'The Unveiling. An introduction to a collection' introduces the visitor of the MTVP Museum Domburg to important works from the European collection of paintings managed by the ICEAC, the International Centre for the Research and Documentation of European Artists, Colonies in Domburg. With work by, among others: Jan Toorop, Ferdinand Hart Nibbrig, Jacoba van Heemskerck, Mies Elout-Drabbe, Lodewijk Schelfhout, Maurice en Sárika Góth, Jeanne Bieruma Oosting, James McNeill Whistler, Herman Heijenbrock, Pieter de Josselin de Jong, Rik Roland Holst, Willem Witsen, Marius Bauer, Otto van Rees, Jan Sluijters, Paul Gabriël, Willem Roelofs, Théophile de Bock, Vilmos Huszár, Bram van Velde, Jan Wiegers, Remko Watjer, Max Liebermann, Paul Müller-Kaempff, Heinrich Vogeler, David en Pieter Oyens, Charles Tschaggeny, Edgard Farasyn, Emmanuel Viérin, Maurice Denis, Vanessa Bell, Emil Nolde, Max Pechstein, Karl Schmidt-Rottluff, Wassily Kandinsky, Franz Marc, Erich Heckel, Lyonel Feininger, Adolf Hölzel, Kurt Schwitters, Carry van Biema, Ida Kerkovius, Hannah Höch, Oskar Kokoschka en Julia Maurer. Exhibition: Marie Tak van Poortvliet Museum, Domburg, The Netherlands (11.09.2021 - 19.06.2022)
Colofon: Dit Cahier verschijnt ter gelegenheid van de tentoonstelling "De Onthulling. Kennismaking met een collectie" in het MTVP Museum Domburg (11 sept. 2021 - 19 juni 2022)
Keywords: ICEAC; Geschichte 1880-2020; Sammlung; Arbeiten auf Papier; Malerei; Ausstellungskatalog -- Marie Tak van Poortvliet Museum -- 11.09.2021-19.06.2022 -- Domburg